Religious Coping and Post-traumatic Growth among Women Survivor of Intimate Partner Violence: A Literature Review - Dinhudayah, Zakiyah; Kilis, Grace (Universitas Negeri Padang, 2024)
Intimate Partner Violence (IPV) refers to violence inflicted by partners that can result in traumatic consequences for the victim. IPV not only adversely affects both physical and mental health but could also enable individuals to achieve positive changes after trauma, a phenomenon recognized as Post Traumatic Growth (PTG). PTG is intricately linked with various factors, one noteworthy factor being coping strategies. Among these strategies, religious coping is a significant approach that individuals adopt when confronted with difficulties and challenges. This research seeks to conduct a literature review on studies related to understanding posttraumatic growth and examining the role of religious coping in the recovery process of individuals who have experienced IPV. The method of this reserach is based on the De Klerk & Pretorius (2019), which follows these steps: (1) selecting reserach topic, (2) finding relevant resources, (3) selecting key liteature (4) data extraction (5) analyzing data, (6) presenting the findings, and (7) drawing conclusions. A total of 23 articles from 2014 to 2024 were eligible and analyzed to explore the relationship between PTG and religious coping among IPV survivors. Results of the present review suggest that religious coping is associated with PTG by transforming meaning in life, using faith and religious practices as a source of personal strength, and improving relationships with others. These aspects are aligned with the domains of PTG, namely changes in outlook on life, perception of self, and experience of relationships with others. This findings provides implications for practitioners to integrate religious coping strategies into the recovery process of IPV survivors to help them promote growth.